Comparison of Approaches to Stability Testing of Medicines in the Russian Federation and the Eurasian Economic Union - A. I. Belanova (Ведомости Научного центра экспертизы средств медицинского применения, 2021)
Stability testing gives necessary data on the effect of such factors as temperature, light, humidity, etc. on the medicinal product quality. The results of these studies help to select suitable primary and secondary packaging and to determine storage conditions and shelf life for the product. The aim of this study was to compare current requirements for stability testing of medicinal products in the Russian Federation and the Eurasian Economic Union (EAEU). The study covered stability testing of small-molecule medicines. The paper describes evolution of approaches to stability testing in the Russian Federation. It summarises the main differences in basic requirements for stability testing as stipulated in the State Pharmacopoeia of the Russian Federation (Ph. Rus.) XIII edition, Ph. Rus. XIV edition, and EAEU regulations. The study demonstrated that the Russian Federation lacks regulations containing specific requirements for stability testing performed to support variations to marketing authorisation documentation. The Ph. Rus. XIV edition does not specify the extent of stability testing to be performed after switching to another manufacturer of the active ingredient or introduction into operation of a new manufacturing site where the medicinal product will be produced. At the same time, the EAEU regulatory documents contain requirements for stability testing for each type of the most frequent variations to marketing authorisation documentation. The study demonstrated the continuing relevance of bringing the Russian regulations on stability testing in line with those of the EAEU.